The potential impact of adverse aircraft-pilot couplings on the safety of tilt-rotor operations - Padfield, Gareth D.; Lu, Linghai (Cambridge University Press, 2022)
This paper addresses the potential impact of adverse aircraft-pilot couplings on tiltrotor safety, when a pilot or autopilot attempts to constrain flight dynamics with strong control. The work builds on previously published research on the theory and application of constrained flight to fixed- and rotary-wing aircraft. Tiltrotor aircraft feature characteristics from both types of aircraft and how these determine behaviour in a unique manner is investigated using a FLIGHTLAB simulation model of the XV-15 aircraft. Two different scenarios are explored in detail, using linearised models that reflect the flight-physics of stability for small deviations from trim. First, the control of vertical flight path with longitudinal cyclic pitch and elevator, and the consequences for the stability of the aircraft surge mode and short-period pitch-heave mode. The classical surge-mode instability for flight at speeds below minimum power is shown to apply to the tiltrotor in helicopter mode but alleviated in conversion and airplane modes. The impact on the short–period mode is seen to be a trade-off between the stabilising pitch attitude and destabilising incidence (angle-of-attack) contributions to the flight-path angle. The second example concerns strong control of roll attitude in the presence of adverse aileron-yaw. Here, the yaw-sway motion can be driven unstable, a problem encountered on fixed-wing aircraft with weak weathercock stability, but rare in the rotorcraft world. For both examples, the loss of stability is expressed as the change in sign of effective damping or stiffness stability derivatives. The explanatory theory for these non-oscillatory or low-frequency aircraft-pilot couplings is presented, along with interpretations in terms of handling qualities criteria. The paper also addresses the question of how to translate the findings into a form of aeronautical knowledge useful for the pilot training community.
Keywords: Aircraft-pilot couplings; Tiltrotor safety; Stability; Handling qualities